Green Fabrication of Silica with Zinc Oxide as Nanocomposite for Adsorption of Methylene Blue Dye from Aqueous Solution - Maatoq, Shahad Luay; Ali, Inaam Hussein (Universitas Gadjah Mada, 2025)
A nanocomposite of silica and zinc oxide was synthesized by a green route approach by utilizing aspartic acid as a reduction agent of Zn+2 in the precursor ZnSO4·7H2O. Different methods like FTIR, BET surface analysis, SEM, and XRD characterized the resulted Zn-Si NC. The adsorption efficiency of the sample was examined by adjusting some variables to remove methylene blue dye from an aqueous solution. The data were analyzed using different models for studying the behavior of the synthesized sample. The Freundlich model is a better predictor than the Langmuir model with a high R2. Also, Temkin and Dubinin-Radushkevich (D-R) isotherms were applied and reveal that the adsorption energy calculated using the D-R isotherm was less than 8 kJ mol−1, indicating that the behavior of the process was physisorption. The kinetic data matched exactly with the pseudo-first-order model. The adsorption process is spontaneous due to a negative value of ΔG and exothermic, as the value of ΔH was −9.616 kJ mol−1. The Si-Zn nanocomposite was successfully biosynthesized as a clean adsorbent to remove MB dye from wastewater.